2018
DOI: 10.1002/ece3.4065
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and colony structure of Tapinoma melanocephalum on the islands and mainland of South China

Abstract: Aim Tapinoma melanocephalum is listed as one of the most important invasive pest species in China. Information regarding the patterns of invasion and effects of geographic isolation on the population genetics of this species is largely lacking.LocationSouth China.MethodsTo address this problem, we genotyped 39 colonies (two colonies were collapsed due to genetic similarity) using microsatellite markers and mitochondrial DNA sequencing to compare colony genetic structure of T. melanocephalum on the mainland and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 75 publications
2
14
0
Order By: Relevance
“…The small number of microsatellite loci used and their capability of detecting the true population structure is another plausible explanation for the discrepancy between this marker and mtDNA. Other recent studies using a similar number of microsatellite markers in other organisms (Pérez-Alquicira et al, 2018;Villamor et al, 2018;Zheng et al, 2018) also found significant genetic structure in some cases. Another study using the same microsatellite loci found significant genetic differentiation in N. squamipes samples from a very small geographic area (maximum distance among sites = 6 km).…”
Section: Discussionsupporting
confidence: 63%
“…The small number of microsatellite loci used and their capability of detecting the true population structure is another plausible explanation for the discrepancy between this marker and mtDNA. Other recent studies using a similar number of microsatellite markers in other organisms (Pérez-Alquicira et al, 2018;Villamor et al, 2018;Zheng et al, 2018) also found significant genetic structure in some cases. Another study using the same microsatellite loci found significant genetic differentiation in N. squamipes samples from a very small geographic area (maximum distance among sites = 6 km).…”
Section: Discussionsupporting
confidence: 63%
“…The small number of microsatellite loci used and their capability of detecting the true population structure is another plausible explanation for the discrepancy between this marker and mtDNA. Other recent studies using a similar number of microsatellite markers in other organisms ( Pérez-Alquicira et al, in press ; Villamor, Costantini & Abbiati, in press ; Zheng et al, in press ) also found significant genetic structure in some cases. Another study using the same microsatellite loci ( Maroja, Almeida & Seuánez, 2003 ) found significant genetic differentiation in N. squamipes samples from a very small geographic area (maximum distance among sites = 6 km).…”
Section: Discussionsupporting
confidence: 63%
“…In the Argentine ant Linepithema humile, the size and the number of supercolonies differ among its various invasive populations, which consist of one to five supercolonies ranging from 1 to 6,000 km long (Björkman-Chiswell, Wilgenburg, Thomas, Swearer, & Elgar, 2008;Buczkowski, Vargo, & Silverman, 2004;Corin, Abbott, Ritchie, & Lester, 2007;Giraud, Pedersen, & Keller, 2002;Hirata, Hasegawa, Toita, & Higashi, 2008;Suhr, McKechnie, & O'Dowd, 2009;Suhr, O'Dowd, McKechnie, & Mackay, 2011;Thomas, Payne-Makrisâ, Suarez, Tsutsui, & Holway, 2006;Vogel, Pedersen, Giraud, Krieger, & Keller, 2010). To date, the combination of polygyny, colony budding dispersal, and unicolonial structure has been described in many invasive ants species, including the most widespread and destructive ones (reviewed in Holway et al, 2002), such as L. humile (Giraud et al, 2002), Lasius neglectus (Cremer, Ugelvig, & Drijfhout, 2008), Wasmannia auropunctata (Fournier et al, 2005), P. megacephala (Fournier et al, 2009), Monomorium pharaonis (Buczkowski & Bennett, 2009;Schmidt, d'Ettorre, & Pedersen, 2010), M. floricola (Wetterer, 2010), A. gracilipes (Thomas et al, 2010), N. fulva (Eyer, McDowell, et al, 2018), Tapinoma melanocephalum (Zheng, Yang, Zeng, Vargo, & Xu, 2018), and the polygyne form of Solenopsis invicta (Fletcher, Blum, Whitt, & Temple, 1980). Interestingly, these strategies have also been reported in a lesser extend in the invasive ant Brachyponera chinensis (Eyer, Matsuura, et al, 2018), in the tramp ant species of the genus Cardiocondyla (Heinze, Cremer, Eckl, & Schrempf, 2006) and in introduced populations of the termite Reticulitermes urbis (Leniaud, Pichon, Uva, & Bagnères, 2009).…”
Section: Introductionmentioning
confidence: 99%